Screening for genomic rearrangements in BRCA1 and BRCA2 genes in Czech high-risk breast/ovarian cancer patients: high proportion of population specific alterations in BRCA1 gene - Stružinská, Ivana; Kleibl, Zdeněk; Stříbrná, Jana; Kotlas, Jaroslav; Zimovjanová, Martina; Matějů, Martin; Zikán, Michal; Pohlreich, Petr (Breast cancer research and treatment, 2010)
Large genomic rearrangements (LGR) represent substantial proportion of pathogenic mutations in the BRCA1 gene, whereas the frequency of rearrangements in the BRCA2 gene is low in many populations. We screened for LGRs in BRCA1 and BRCA2 genes by multiplex ligation-dependent probe amplification (MLPA) in 521 unrelated patients negative for BRCA1/2 point mutations selected from 655 Czech high-risk breast and/or ovarian cancer patients. Besides long range PCR, a chromosome 17-specific oligonucleotide-based array comparative genomic hybridization (aCGH) was used for accurate location of deletions. We identified 14 patients carrying 8 different LGRs in BRCA1 that accounted for 12.3% of all pathogenic BRCA1 mutations. No LGRs were detected in the BRCA2 gene. In a subgroup of 239 patients from high-risk families, we found 12 LGRs (5.0%), whereas two LGRs were revealed in a subgroup of 282 non-familial cancer cases (0.7%). Five LGRs (deletion of exons 1-17, 5-10, 13-19, 18-22 and 21-24) were novel; two LGRs (deletion of exons 5-14 and 21-22) belong to the already described Czech-specific mutations; one LGR (deletion of exons 1-2) was reported from several countries. The deletions of exons 1-17 and 5-14, identified each in four families, represented Czech founder mutations. The present study indicates that screening for LGRs in BRCA1 should include patients from breast or ovarian cancer families as well as high-risk patients with non-familial cancer, in particular cases with early-onset breast or ovarian cancer. On the contrary, our analyses do not support the need to screen for LGRs in the BRCA2 gene. Implementation of chromosome-specific aCGH could markedly facilitate the design of primers for amplification and sequence analysis of junction fragments, especially in deletions overlapping gene boundaries.
Keywords: Mutagenesis, Insertional; Sequence Deletion; dospělí; Comparative Genomic Hybridization; Point Mutation; introny; Molecular Sequence Data; Predictive Value of Tests; nádory prsu; plošný screening; genová přestavba; Gene Rearrangement; srovnávací genomová hybridizace; Genetic Predisposition to Disease; genetická predispozice k nemoci; lidé středního věku; sekvenční delece; rodokmen; Genetic Testing; Humans; Mass Screening; Middle Aged; Pedigree; inzerční mutageneze; Polymerase Chain Reaction; nádory vaječníků; Czech Republic; Introns; Breast Neoplasms; Chromosome Breakpoints; Risk Factors; Česká republika; sekvence nukleotidů; bodová mutace; Adult; Risk Assessment; polymerázová řetězová reakce; rizikové faktory; BRCA2 Protein; mutační analýza DNA; Exons; BRCA1 Protein; molekulární sekvence - údaje; ženské pohlaví; Female; DNA Mutational Analysis; hodnocení rizik; exony; Ovarian Neoplasms; lidé; body zlomu chromozomu; prediktivní hodnota testů; protein BRCA1; genetické testování; Haplotypes; haplotypy; Base Sequence; protein BRCA2